Catalytic cracking of pyrolytic oil derived from arabica coffee parchment using Ni-NZ catalysts - Nisa, Syarifah Rahimatun; Setiawan, Adi; Syam, Azhari Muhammad; Rahmawati, Cut Aja; Rizkina, Shafira (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2025)
The potential of bio-oil derived from biomass has garnered significant attention among researchers due to its prospects as an environmentally friendly fuel alternative. This study utilized bio-oil extracted from Arabica coffee parchment sourced from coffee plantations in Bener Meriah Regency, Aceh, Indonesia. Nickel metal was used as a catalyst impregnated into natural zeolites to accelerate the reaction rate in the catalytic cracking method. The catalyst was prepared using the wet impregnation method, with natural zeolites first activated using 1 N HCl. During the impregnation process, stirring was conducted for 6 hours at 25 °C, followed by drying in an oven at 115 °C for 12 hours, and calcination at 500°C for 4 hours. The resulting catalyst was then characterized using TGA, XRD, and SEM analyses to determine the optimal catalyst properties. Based on XRD analysis across various concentrations, curves were observed at angles 2θ ≈ 37° and 44°, which are presumed to be peaks of nickel catalysts on the zeolite surface. In this study, the Ni-NZ catalyst concentration was varied to 15%, 20%, and 25% (w/w). GC-MS chromatogram results indicated that the highest formation of bio-benzene occurred at a 25% catalyst concentration with a residence time of 2 hours, yielding 9.28%. The findings suggest that Ni-NZ catalysts are technically capable of producing aromatic hydrocarbons from the pyrolytic oil of coffee parchment, which can be utilized as a biofuel component